1992
DOI: 10.1159/000118891
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Imbalance in Major Depressive and Panic Disorders

Abstract: We investigated subsets of peripheral immunologic cells in 12 drug-free patients affected by major depression according to DSM-III-R criteria, and who had recent evidence of somatic diseases. They were compared with 10 drug-free depressives, with 10 patients with panic disorder, and with 12 healthy volunteers, all without somatic disease. The immune subsets were measured by flow cytometry. The results showed that both groups of depressives had the same abnormalities in immune cells compared with the healthy vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 10 publications
3
28
0
Order By: Relevance
“…At present, the population of lymphocytes presenting 5HT transporter still has to be determined, but it is clear that a selective subtype of immune-circulating cells may have possible uptake sites for 5HT, but confi rmation in immune cells is lacking. CD3+ cells, which coexpress CD4+ and CD8+ antigens [38,39] , were counted and this group of depressed patients had a low number of positive CD3+ cells, in agreement with a previous study [40] . Further studies will be required to identify the distribution of these proteins on immune cells and the ensuing functional implications in health and disease.…”
Section: P42 C43 P44 P51 C52supporting
confidence: 88%
“…At present, the population of lymphocytes presenting 5HT transporter still has to be determined, but it is clear that a selective subtype of immune-circulating cells may have possible uptake sites for 5HT, but confi rmation in immune cells is lacking. CD3+ cells, which coexpress CD4+ and CD8+ antigens [38,39] , were counted and this group of depressed patients had a low number of positive CD3+ cells, in agreement with a previous study [40] . Further studies will be required to identify the distribution of these proteins on immune cells and the ensuing functional implications in health and disease.…”
Section: P42 C43 P44 P51 C52supporting
confidence: 88%
“…The authors used the plaque-forming cell assay and performed basal measures only, which may explain the discongruency between their results and ours. In a number of studies in depression, changes in T cells, B cells, or T cell subsets have been reported, though the results are conflicting (Schleifer et al 1989: Marazziti et al 1992. Quantative changes in the distribution of these parameters could be an inherent feature in depression, irrespective of plasma cortisol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation with anti-CD3+ induced significantly lower expression of CD25+ in generalized anxiety disorder patients when compared to controls [4]. In addition, patients with panic disorder had significantly lower CD4+ levels than healthy controls and depressive disorder patients [5]. In contrast, panic disorder patients had significantly higher levels of T4 [6, 7], natural killer cells, CD19 cells (B lymphocytes), human leukocyte antigen-DR-presenting cells [8], serum immunoglobulin A (IgA) [7]and interleukin (IL)-2 [9]than normal controls.…”
Section: Introductionmentioning
confidence: 99%